2019
DOI: 10.1103/physrevlett.122.015701
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Time Crystals in the Absence of Manifest Symmetries or Disorder in Open Quantum Systems

Abstract: We establish a link between metastability and a discrete time-crystalline phase in a periodically driven open quantum system. The mechanism we highlight requires neither the system to display any microscopic symmetry nor the presence of disorder, but relies instead on the emergence of a metastable regime. We investigate this in detail in an open quantum spin system, which is a canonical model for the exploration of collective phenomena in strongly interacting dissipative Rydberg gases. Here, a semi-classical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 81 publications
(132 reference statements)
0
96
1
Order By: Relevance
“…This corresponds to the case where a metastable state in the undriven system exists, it is necessary to have DTC. We further find that even the undriven system is not in the self-trapping regime, the periodic drive can also turn the system to a DTC, this interesting result is quite different from the earlier studies, for example in [13] the appearance of DTC requires meta-stable states in the undriven system. In addition, we show that period-n (n>2) DTC can be realized in large rings based on two-site systems considered here.…”
Section: Introductioncontrasting
confidence: 95%
See 2 more Smart Citations
“…This corresponds to the case where a metastable state in the undriven system exists, it is necessary to have DTC. We further find that even the undriven system is not in the self-trapping regime, the periodic drive can also turn the system to a DTC, this interesting result is quite different from the earlier studies, for example in [13] the appearance of DTC requires meta-stable states in the undriven system. In addition, we show that period-n (n>2) DTC can be realized in large rings based on two-site systems considered here.…”
Section: Introductioncontrasting
confidence: 95%
“…The extension of DTC to open quantum system with drive and dissipation attracts widespread research interest recently. Concrete models [12,13] shown that the DTC order can exist in open system with appropriately engineered drive and dissipation. This prediction was confirmed by the authors of [12] who shown that the modified Dicke model with the help of sufficiently strong atom-photon coupling and photon loss can exhibit time crystalline structure, and the same prediction was reported in [13] that a dissipative Rydberg model is also possible to possess time crystal order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this quest for phases of quantum matter without equilibrium counterpart, time crystals (TCs) represent a promising candidate for a novel form of dynamical order out-of-equilibrium. In TCs, observables dynamically entrain at a frequency subharmonic of the one imposed by an external periodic drive [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and they have been currently realized with trapped ions [19] and solid state systems [20][21][22]. In most previous studies, TCs are realized in closed interacting quantum many-body systems, which are prone to heating towards an infinite temperature state under the action of periodic drive [23,24], therefore, a slowdown of energy absorption is customarily entailed via a disorder induced many-body localized phase [25][26][27][28], or by fast driving [8,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The open nature is common to a vast class of modern experimental platforms in quantum science and technology, such as photonic systems [4], ultracold atoms [5-9], optomechanical systems [10][11][12][13] or superconducting circuits [14][15][16], for which driving and losses are omnipresent. Open quantum systems also display emergent physics, in particular dissipative phase transitions and topological phases [40][41][42][43][44][45].Several studies have highlighted the possibility for a continuous-wave driven-dissipative quantum system to reach a non-stationary state in the long time limit in which undamped oscillations arise spontaneously [46][47][48][49][50][51][52]. This phenomenon has been dubbed as boundary or dissipative time crystal (DTC), in analogy with the time crystals in some Hamiltonian systems [53].…”
mentioning
confidence: 99%